(untitled) (Research, Society and Development, 2024)
Objectives: To identify strategies to prevent problems associated with alcohol abuse in adolescents and to explore nursing interventions to prevent harm associated with alcohol abuse. Methodology: Integrative Literature Review (ILR), based on primary, quantitative, and observational studies obtained through search engines PubMed, B-On, and databases Medline and CINAHL. We used the PICOD method for the research, selecting seven articles published between 2019 and 2023. Results: The studies analyzed the effectiveness of different interventions in reducing alcohol consumption among adolescents, highlighting the importance of implementing evidence-based prevention programs in schools. Such programs address specific risk factors and use context-appropriate strategies. Selective prevention targeted at personality, such as the PreVenture program, demonstrated long-term effects in reducing alcohol-related harm over several years. These results underscore the continuous need to invest in preventive initiatives to reduce the negative impacts of alcohol consumption among youth. Conclusion: It is pertinent to address the issue of alcohol abuse in adolescence early through effective prevention strategies. It is crucial to involve not only adolescents but also their families, educators, and the entire educational community for a more significant impact.